Mitochondrial Ataxias: Molecular Classification and Clinical Heterogeneity - Piervito Lopriore; Valentina Ricciarini; Gabriele Siciliano; Michelangelo Mancuso; Vincenzo Montano (MDPI AG, 2022)
Ataxia is increasingly being recognized as a cardinal manifestation in primary mitochondrial diseases (PMDs) in both paediatric and adult patients. It can be caused by disruption of cerebellar nuclei or fibres, its connection with the brainstem, or spinal and peripheral lesions leading to proprioceptive loss. Despite mitochondrial ataxias having no specific defining features, they should be included in hereditary ataxias differential diagnosis, given the high prevalence of PMDs. This review focuses on the clinical and neuropathological features and genetic background of PMDs in which ataxia is a prominent manifestation.